Relationship Between Parents’ Parenting And Independence Level Of Activity Daily Living (ADL) In Soft Mental Retardation Children - Desak Made Ari Dwi Jayanti; R. Tri Rahyuning Lestrai; Ni Putu Riskayanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
ABSTRACTIntroduction: Mental retardation children are children who have a lack of intelligence from the time of their development. Parenting is very influential on the independence of children with mild mental retardation because good parenting from parents will help mild mental retarded children to fulfill their activity daily living needs (ADL) independently. The purpose of this study was to determine the relationship of parenting parents with an independent level of activity daily living (ADL) in children with mild mental retardation in Tabanan 1 State SLB. Method: This study uses descriptive correlational design with cross sectional approach. The number of samples used was 51 respondents, using total sampling technique with a test using Chi-Square. Results: results obtained by parents using democratic parenting as many as 40 respondents (78.4%), while for the level of independence of daily living activities (ADL) in mild mental retarded children categorized as independent as many as 27 people (52.9%), obtained a number p value is 0,002 (p <0,05) so there is a correlation between parenting style with the level of independence of daily living activity (ADL) in mild mental retarded children in SLB 1 Tabanan. Discussion: It is recommended that parents apply proper parenting to their children and provide sertadorongan motivation to their children to explore the potential abilities of children, especially in terms of independence of activity daily living (ADL). Keywords: Parenting, Activity Daily Living, Mild Mental Retardation Children